Analysis of the Misconceptions of Class XII High School Students in Pekanbaru by Using the Certainty of Response Index (CRI) - Dita Deanesia; Sri Wulandari; Zulfarina Zulfarina (Universitas Riau, 2021)
One of the misconceptions can be identified by using CRI (Certainty of Response Index). The purpose of this study was to identify the misconceptions of class XII high school students in the city of Pekanbaru on the material of Photosynthesis and Plant Respiration using the Certainty of Response Index (CRI) method. This research is a survey research. The location of this research was carried out at two high schools in Pekanbaru, namely SMA N 15 Pekanbaru and SMA IT Az-Zuhra Pekanbaru. The number of samples in this study is the total population of the two SMAs. The data collection technique was carried out using a written test instrument in the form of a multiple choice test accompanied by CRI. The average percentage of students' misconceptions of SMA IT AZ-ZUHRA and SMAN 15 Pekanbaru on the concept of photosynthesis, the highest percentage is in the sub-concept of the benefits of photosynthesis for plants by 96.15% and the lowest percentage is in the sub-concept of photosynthetic pigments at 53.19%. The average percentage of students' misconceptions at SMA IT AZ-ZUHRA and SMAN 15 Pekanbaru on the concept of plant respiration, the highest percentage is found in the sub-concept of understanding respiration in plants of 84.62%. The lowest percentage is found in the sub-concept of understanding breathing and the sub-concept of when plants breathe, each of which is 67.58%.